2016
DOI: 10.1007/s00170-016-9456-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of friction conditions on finite element simulation of microscale machining with the presence of built-up edge

Abstract: In micromachining, the uncut chip thickness is less than the cutting tool edge radius, which results in a large negative effective rake angle. Depending on the material properties, this large negative rake angle promotes built-up edge (BUE) formation. A stable BUE acts like a cutting edge and affects the mechanics of the process. The size of the BUE increases with increasing uncut chip thickness and cutting speed. It also creates a positive rake angle, but it decreases the clearance angle of the tool. A method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Furthermore, F f was the same in the Vc range from 90 to 120 m/min. A similar thermal softening of a workpiece was previously observed by Samad Nadimi Bavil Oliaei [ 37 ], where they found that the presence of a built-up edge affects the thrust forces more than the cutting forces.…”
Section: Resultssupporting
confidence: 76%
“…Furthermore, F f was the same in the Vc range from 90 to 120 m/min. A similar thermal softening of a workpiece was previously observed by Samad Nadimi Bavil Oliaei [ 37 ], where they found that the presence of a built-up edge affects the thrust forces more than the cutting forces.…”
Section: Resultssupporting
confidence: 76%
“…It is worth mentioning that different heat transfer coefficients are used in the literature to simulate orthogonal cutting processes. For instance, Calamaz et al (2008) used a value of 20,000 (W/m 2 °C), Karpat (2010) used a value of 10,000 (W/m 2 °C), Sima and Özel (2010) have used 1000 (kW/m 2 K), while Oliaei and Karpat (2017 b ) have used 5000 (W/m 2 °C). This is mainly because the simulation time for the machining is very short.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the above point, in addition to tool life, the surface finish of the machined part is an equally important requirement. During dry machining of an aluminium alloy, the tool wear is mainly caused due to the formation of an adhesive aluminium layer and built-up *For correspondence edge [3][4][5]. This also greatly affects the surface finish of the machined surface.…”
Section: Literature Reviewmentioning
confidence: 99%